1991
DOI: 10.1111/j.1365-2141.1991.tb08586.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary thrombocythaemia in pregnancy

Abstract: Nine pregnancies in six patients with primary thrombocythaemia are reported. Eight pregnancies resulted in the delivery of normal infants. One pregnancy ended in spontaneous abortion at 7 weeks gestation. One pregnancy was complicated by superficial thrombophlebitis and a postpartum haemorrhage. We suggest that pregnancy in patients with primary thrombocythaemia can have a favourable outcome, but requires close monitoring. Administration of aspirin during pregnancy may be of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 11 publications
5
39
0
1
Order By: Relevance
“…Of the 18 studies that reported VTE outcomes and antepartum LMWH prophylaxis use, there were 0 antepartum VTE events among 82 pregnancies with LMWH use (0%; 95% CI, 0.0-5.7; I 2 0%), and 8 antepartum VTE events among 407 pregnancies without LMWH use (2.5%; 95% CI, 1.3-4.3; I 2 0%) ( Table 2). [4][5][6][7][14][15][16][17][18][19][20][21][22][23]25,[28][29][30][31] Among the 18 studies that reported VTE outcomes and ASA use during pregnancy, there were 6 antepartum VTE events among 283 pregnancies with ASA use (2.9%; 95% CI, 1.3-5.1; I 2 0%), and 2 antepartum VTE events among 158 pregnancies without ASA use (2.8%; 95% CI, 0.9-5.8; I 2 0%). Of the subgroup of 212 pregnancies reported in which ASA was used alone without LMWH, there were 6 antepartum VTE events (4.2%; 95% CI, 2.0-7.1; I 2 0%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 studies that reported VTE outcomes and antepartum LMWH prophylaxis use, there were 0 antepartum VTE events among 82 pregnancies with LMWH use (0%; 95% CI, 0.0-5.7; I 2 0%), and 8 antepartum VTE events among 407 pregnancies without LMWH use (2.5%; 95% CI, 1.3-4.3; I 2 0%) ( Table 2). [4][5][6][7][14][15][16][17][18][19][20][21][22][23]25,[28][29][30][31] Among the 18 studies that reported VTE outcomes and ASA use during pregnancy, there were 6 antepartum VTE events among 283 pregnancies with ASA use (2.9%; 95% CI, 1.3-5.1; I 2 0%), and 2 antepartum VTE events among 158 pregnancies without ASA use (2.8%; 95% CI, 0.9-5.8; I 2 0%). Of the subgroup of 212 pregnancies reported in which ASA was used alone without LMWH, there were 6 antepartum VTE events (4.2%; 95% CI, 2.0-7.1; I 2 0%).…”
mentioning
confidence: 99%
“…Among the 16 studies that reported VTE outcomes and IFN use during pregnancy, there were 0 antepartum VTE events among 38 pregnancies with IFN use (0%; 95% CI, 0.0-11.9; I 2 0%), and 3 antepartum VTE events among 266 pregnancies without IFN use (2.0%; 95% CI, 0.7-3.9; I 2 0%). 6,[14][15][16][17][18][19][20][21][22][23]25,[28][29][30][31] Of the 38 pregnancies with IFN use: 14 received LMWH, 14 received no LMWH, and 10 had unknown LMWH use. Of the 266 pregnancies without IFN: 30 received LMWH, 156 received no LMWH, and 80 had unknown LMWH use.…”
mentioning
confidence: 99%
“…Most of the patients have a history of abortions in the past [13,14]; nevertheless, pregnancy complications including intrauterine growth retardation and preeclampsia have been reported [15]. Platelet apheresis was also performed complementary with ASA and low-molecular weight heparin (LMWH) [16,17].…”
Section: Platelet Apheresismentioning
confidence: 99%
“…Due to the increased percentage of abortions and pregnancy complications in untreated patients as results of thrombosis and abnormal placenta blood circulation, the addition of low-dose ASA showed encouraging results. There are reports in patients with a history of abortions that had a successful pregnancy after single treatment with ASA [5,6,8,9,16,[19][20][21][22][23][24][25]. ASA was also initiated in some cases, if not at the beginning of pregnancy, when a pregnancy complication was present like hypertension disorders, abrutio placenta or IUGR and premature delivery [5,8,[25][26][27].…”
Section: Low Dose Aspirin and Other Antiplatelet Agentsmentioning
confidence: 99%
See 1 more Smart Citation